Economic impact of heart failure with preserved ejection fraction: insights from the ALDO‐DHF trial - Djawid Hashemi; Ludwig Dettmann; Tobias D. Trippel; Volker Holzendorf; Johannes Petutschnigg; Rolf Wachter; Gerd Hasenfuß; Burkert Pieske; Antonia Zapf; Frank Edelmann (ESC Heart Failure)
Abstract Aims Although heart failure (HF) with preserved ejection fraction (HFpEF) is a leading cause for hospitalization, its overall costs remain unclear. Therefore, we assessed the health care‐related costs of ambulatory HFpEF patients and the effect of spironolactone. Methods and results The aldosterone receptor blockade in diastolic HF trial is a multicentre, prospective, randomized, double‐blind, placebo‐controlled trial conducted between March 2007 and April 2011 at 10 sites in Germany and Austria that included 422 ambulatory patients [mean age: 67 years (standard deviation: 8); 52% women]. All subjects suffered from chronic New York Heart Association (NYHA) class II or III HF and preserved left ventricular ejection fraction of 50% or greater. They also showed evidence of diastolic dysfunction. Patients were randomly assigned to receive 25 mg of spironolactone once daily (n = 213) or matching placebo (n = 209) with 12 months of follow‐up. We used a single‐patient approach to explore the resulting general cost structure and included medication, number of general practitioner and cardiologist visits, and hospitalization in both acute and rehabilitative care facilities. The average annual costs per patient in this cohort came up to €1, 118 (±2,475), and the median costs were €332. We confirmed that the main cost factor was hospitalization and spironolactone did not affect the overall costs. We identified higher HF functional class (NYHA), male patients with low haemoglobin level, with high oxygen uptake (VO2max) and coronary artery disease, hyperlipidaemia, and atrial fibrillation as independent predictors for higher costs. Conclusions In this relatively young, oligosymptomatic, and with regard to the protocol without major comorbidities patient cohort, the overall costs are lower than expected compared with the HFrEF population. Further investigation is needed to investigate the impact of, for example, comorbidities and their effect over a longer period of time. Simultaneously, this analysis suggests that prevention of comorbidities are necessary to reduce costs in the health care system.